Volcano Tourism of Mt. Rinjani in West Nusa Tenggara Province, Indonesia: a Volcanological and Ecotourism Perspective - Rachmat, Heryadi (Berita Sedimentologi, 2012)
Indonesia has nearly 500 volcanoes and 129 of them are currently active. The active volcanoes are spread out along a 7000 km volcanic belt from Sumatra to Java, Bali, Nusa Tenggara, Banda, Halmahera and Sulawesi. Each volcano possesses its own natural characteristics that usually include beautiful landscapes and sceneries, fresh air and fertile lands. One of the volcanoes is Mount (Mt.) Rinjani (+3726 m) in Lombok island, West Nusa Tenggara. It is the second highest volcano in Indonesia after Mt. Kerinci (+3800 m) in Sumatra. Mt. Rinjani is situated at latitude 8°25' S and longitude 116°28' E. The Rinjani volcano complex has potential to be developed for volcano tourism and natural volcanic museum.Currently, vulcano tourism in Indonesia is still poorly developed and it relies on resources-based tourism only, not on knowledge-based tourism. Now is the moment for volcano tourism stakeholders, including travel guides, to prepare themselves by gaining more knowledge, specifically in term of scientific knowledge of a volcano and its environment. By doing so, they can make volcano more interesting as a tourist attraction and more appealing to both domestic and foreign tourists. The tourists eventually can have better understanding of a volcano including the landscapes, sceneries and panoramas, calderas, lakes, hotsprings, waterfalls, caves, etc.This paper discusses the volcano-tourism potential of Mt. Rinjani, focusing on volcanic and geological aspects as the main tourist attraction, and environmental aspect as a secondary attraction. The volcano-tourism attractions can include specific or general activities, depending on a visitor's interest, for examples for recreation, adventure or cultural activities.